Multinational Corporation, International Unions and Industrial Relations : The Canadian Case - Crispo, John (Relations industrielles / Industrial Relations, 1974)
This paper highlights several generalizations about the conduct in Canada of both multi-national corporations and international unions. Their impact on Canadian collective bargaining is examined and sets the stage for a discussion of selected issues and problems growing out of their presence.